The Determinants of Audit Delay with Profitability as a Moderating Variable in State-Owned Enterprises in Indonesia - Christin, Mouly Nataly; Safriliana, Retna (Jurnal Akuntansi Aktual, 2026)
Purpose: This study purpose to analyzes the effects of leverage, audit committee size, audit opinion, and auditor reputation on audit delay, with profitability as a moderating variable Method: The method of this study uses quantitative research with explanatory method. The sample consists of 29 SOEs listed on the Indonesia Stock Exchange during the period 2022–2024, resulting in 87 firm-year observations. Hypothesis testing was conducted using multiple linear regression to examine the direct effects of the independent variables on audit delay, followed by Moderated Regression Analysis (MRA) to test the moderating role of profitability. Findings: The findings of this research, indicate that leverage does not have a significant effect on audit delay, suggesting that debt-related risk does not necessarily prolong audit completion in SOEs. In contrast, audit committee size and auditor reputation have a positive and significant effect on audit delay, reflecting increased monitoring intensity and audit rigor. Furthermore, profitability strengthens the positive relationship between these governance and audit-quality factors and audit delay, but does not moderate the leverage–audit delay relationship. Originality/Value: This study contributes to the literature by integrating agency and signaling theories in the context of SOEs, highlighting the trade-off between audit quality and reporting timeliness. It provides critical insights for policymakers and SOE management in balancing accountability with efficiency in financial reporting.